Analysis of the deployment of a three-mass tethered satellite formation. Issue 1 (November 2020) - Chen, Shumin; Li, Aijun; Wang, Changqing
Abstract: Tethered satellite formation has obtained widespread attention in recent years. The main causes of the increasing study interest around tethered formation lie in its promised applications in space, such as interferometric measurements. The deployment of a tethered formation system in low Earth orbit is investigated in this paper. The orbital tethered system consists of three nanosatellites connected via tethers end-to-end, and the desired arrangement for the end masses is an equilateral triangle. For the sake of brevity, the formation system is modeled as a particle-rigid rod system, in which the elasticity of the tethers is omitted. The deployment process is carried out using tension forces and active external forces generated by low-thrust engines. The numerical results confirm that it is possible to deploy a triangular tethered system, which rotates at a given initial angular velocity, to an expected arrangement using the proposed control law of tether tensions and active forces.